Pengaruh Evaluasi Kinerja dan Motivasi terhadap Promosi Jabatan - Siti Indah Fauzi; Helmi Chaidir (Indonesian Journal of Economics Application (IJEA), 2021)
This study aims to describe and analyze the effect of performance evaluation and motivation on promotion to the position of PT Bank BNI Syariah Kebon Jeruk Branch, West Jakarta. The research design used in data collection was a descriptive quantitative associative method. The sample in this study amounted to 50 employees. The data analysis technique used in this study used validity and reliability test analysis, simple linear regression analysis, correlation coefficient, determination coefficient analysis, and t-test. Based on the research results, it is obtained information that the contribution of the motivation variable and the job appraisal variable has a strong influence on the employee promotion variable, while 7.27 percent. In contrast, the rest is influenced by other factors not examined in this study.